A comparison of cell density and serotonergic innervation of the amygdala among four macaque species. Issue 7 (19th October 2020) - Jones, Danielle N.; Erwin, Joseph M.; Sherwood, Chet C.; Hof, Patrick R.; Raghanti, Mary Ann
Abstract: The genus Macaca is an ideal model for investigating the biological basis of primate social behavior from an evolutionary perspective. A significant amount of behavioral diversity has been reported among the macaque species, but little is known about the neural substrates that support this variation. The present study compared neural cell density and serotonergic innervation of the amygdala among four macaque species using histological and immunohistochemical methods. The species examined included rhesus ( Macaca mulatta), Japanese ( M. fuscata), pigtailed ( M. nemestrina), and moor macaques ( M. maura) . We anticipated that the more aggressive rhesus and Japanese macaques would have lower serotonergic innervation within the amygdala compared to the more affiliative pigtailed and moor macaques. In contrast to our prediction, pigtailed macaques had higher serotonergic innervation than Japanese and moor macaques in the basal and central amygdala nuclei when controlling for neuron density. Our analysis of neural cell populations revealed that Japanese macaques possess significantly higher neuron and glia densities relative to the other three species, however we observed no glia‐to‐neuron ratio differences among species. The results of this study revealed serotonergic innervation and cell density differences among closely related macaque species, which may play a role in modulating subtle differences in emotional processing and species‐typical social styles. Abstract : A high degree of behavioral variation has been observed among macaque species. To investigate the neural basis of this variation, we used stereological methods to compare neural cell density and serotonin transporter‐immunoreactive axon density in the amygdala among four species that differ in social style. We hypothesized that significantly greater serotonergic innervation would be observed in the amygdala of the most socially tolerant species in our sample, the moor macaque. Instead, the pigtailed macaque, which is considered moderately tolerant, possessed significantly greater serotonergic innervation in the amygdala relative to Japanese and moor macaques. Our findings provide insight on the neural substrates of primate sociality from an evolutionary perspective.